Biomechanical comparison of plate-nail vs. plate-rod for experimentally-induced gap fractures in ex vivo canine femora - Mesquita, L. R. [UNESP]; Muzzi, L. A.L.; Lima, J. T.; Muzzi, R. A.L.; Lacreta, A. C.C.; Silva, W. G. (Science Alert, 2015)
The purpose this original article is to compare the mechanical properties of an interlocking nail-plate combination (plate-nail) vs. an intramedullary pin-plate combination (plate-rod) applied to experimentally induced gap fractures in canine femora. Twenty four paired canine femora were assigned to either plate-nail or plate-rod with 2.7 mm or 3.5 mm system constructs. In each femur, a mid-diaphyseal ostectomy was performed and the selected system was applied. Paired system constructs were subjected to compression and bending tests. The maximum load differed significantly between fixation systems. The plate-nail system had greater maximum load than plate-rod system. The strength, stiffness and maximum deformation was similar between plate-rod and plate-nail. The plate-nail system proved to be a good option for diaphyseal long bone fracture fixation in dogs.
Keywords: Bone plate; Femur; Interlocking nail; Intramedullary pin; Loading profile